...in a pluralistic society - Brand, Gerrit (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Questions on religion and pluralism are complicated by the fact that central terms in the discourse, such as “pluralism”, “religion” and the “secular”, can be interpreted in a variety of ways and are also seriously contested. A plausible argument can be advanced to the effect that the problem of religion in a pluralistic society cannot be solved by opting for a kind of secularism that suggests the possibility of a neutral, non-religious public space. An alternative model of pluralism is both conceivable and preferable. Within the latter model a specifically Christian motivation for supporting a pluralistic society has to and can be developed.